Customer Preferences in Housing Loan Selection among Commercial Banks in Nepal - Rijal, Raju; Rijal, Madhu; Bhandari, Rita (Journal of Kathmandu BernHardt College, 2025)
This study investigates the key drivers influencing borrowers’ selection of banks for home loans in Kathmandu Valley. Using a descriptive research design with 412 valid responses analyzed through correlation and regression models, the findings reveal that referrals, EMI (Equated Monthly Installment) provisions, and advertisement significantly affect bank selection, while interest rates, service quality, and reputation, though positively associated, were statistically insignificant. The results highlight that borrowers’ preferences are shaped not only by financial factors but also by social and perceptual influences, underscoring the need for banks to refine strategies that balance competitive pricing, transparency, and customer trust.